Efficacy and Safety of Iclaprim for the Treatment of Skin Structures and Soft Tissue Infections: A Methodological Framework - Wang, Lian; Fan, Jin; Zheng, Linli; Chen, Lingmin (Frontiers in Pharmacology, 2022)
Background: Skin and soft tissue infections (SSTIs) are among the most common infections worldwide. They manifest in a variety of forms, such as erysipelas, cellulitis, and necrotizing fasciitis. Antibiotics are the significant method for clinical treatment of SSTIs. This study reported a methodology framework to determine the efficacy and safety of iclaprim in treatment of SSTIs. Methods: We will search the PubMed, EMbase, CNKI, WanFang Data, VIP, and ClinicalTrials.gov from their inception to June 2022 for randomized controlled trials and cohort studies on iclaprim with SSTIs. Two authors will independently screen the eligible studies, assess the quality of the included papers, and extract the required information. Randomized controlled trials will be assessed using the Cochrane risk-of-bias tool. The Newcastle–Ottawa Scale will be used to evaluate observational studies. The quality of the evidence will be evaluated using the Grading of Recommendations Assessment Development and Evaluation system. RevMan 5.3 will be used for the data synthesis and quantitative analysis. Results and Discussions: This study will provide the clinicians with more high-quality evidence to choose iclaprim for patients with SSTIs. Ethics and Dissemination: This systematic review and meta-analysis will be based on published data, so ethical approval is not necessary. The results of this meta-analysis will be published in a peer-reviewed journal.